2011
DOI: 10.1017/s1431927611012207
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Exacerbates Ventricular Remodeling and Dysfunction in the Volume Overloaded Heart

Abstract: Cigarette smoking is an independent risk factor for heart disease and is linked to sudden cardiac death. In this study, we examined the effects of cigarette smoke (CS) on the volume overload stressed heart. Our hypothesis was that CS exacerbates volume overload (VO)-induced cardiac dysfunction by accelerating ventricular remodeling. VO stress was surgically induced in male Sprague-Dawley rats by abdominal aortocaval fistula (ACF). Rats, with and without ACF, were exposed to either room air or CS (6 cigarettes/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
1
14
2
Order By: Relevance
“…Compensatory hypertrophy due to VO involves remodeling of the ECM, including increased deposition of collagen [32]. Pathological ECM remodeling during LV dilatation involves reorganization of collagen fibrils characterized by increased collagen III and/or reductions in cross-linking, which may contribute to dilatation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory hypertrophy due to VO involves remodeling of the ECM, including increased deposition of collagen [32]. Pathological ECM remodeling during LV dilatation involves reorganization of collagen fibrils characterized by increased collagen III and/or reductions in cross-linking, which may contribute to dilatation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty eight days after CPC implantation in vivo ventricular dimensions and function were assessed as previously described [23] and detailed in the Supplementary Methods.…”
Section: Invasive Left Ventricular Measurementsmentioning
confidence: 99%
“…Many studies have shown that cigarette smoking is associated with deleterious health effects such as heart disease [1], chronic obstructive pulmonary disease, cancer [2], fertility problems [3], and periodontal disease [4]. In cosmetic restorative dentistry, some of the substances coming from tobacco can be absorbed by resin composite, dentin, and enamel surface [5] and lead to tooth/composite discoloration [610].…”
Section: Introductionmentioning
confidence: 99%